Multidisciplinary management of invasive vertebral hemangioma: the role of different neurointervention modalities—a retrospective study - Ahmed Elsayed Sultan; Tamer Hassan; Mohamed Abdelbary; Amr Elwany (Egyptian Journal of Neurosurgery, 2023)
Abstract Background Catastrophic intraoperative bleeding is a major complication of surgical removal of invasive vertebral hemangioma. Interventional neuroradiology techniques could be more useful tools to manage such hemorrhagic lesions. Results Retrospective analysis of cases of invasive vertebral hemangioma revealed 17 cases treated at the Alexandria University School of Medicine from 2006 to 2020. The study included 52.9% of males with a mean age of 38.4 ± 18.6 years old. All patients reported local and sometimes radicular pain; 64.7% exhibited progressive neurological deficits. Imaging revealed thoracic spine affection in 11 cases, lumbar vertebral in four cases, and cervical vertebra in two cases. Vertebral involvement occurred in 10 cases and paravertebral extension in 13 cases. Neurointervention modalities included transarterial embolization followed by corpectomy and fixation (one case with C4 lesion), direct surgery with corpectomy and anterior fixation (one case with C7 lesion), vertebroplasty alone (four cases), vertebroplasty with fixation (seven cases), and direct transpedicular alcohol injection with immediate devascularization and necrosis of the vascular channels inside the lesions (six cases). The alcohol injection use ranged from 4 to 10 ml in each pedicle. All patients did well during the follow-period post-intervention. The neurological deficits improved over six months. All patients showed improved Nurick grade regardless of the intervention (preoperative mean 2.7 ± 1.9 vs. postoperative mean 1.1 ± 1.3, p value 0.0001). Two patients were completely paraplegic, but with intact deep sensation, they improved dramatically and can walk unsupported post-intervention. Conclusions Vertebral hemangioma can present in an invasive manner that necessitates intervention. Preoperative embolization, alcohol injection, or vertebroplasty are helpful methods to decrease intraoperative catastrophic hemorrhage. Alcohol injection is cost-effective with immediate devascularization of the lesion. The extensive 360 surgery utilization can be decreased with the use of alcohol and vertebroplasty. More cases are needed to validate these conclusions.